The Influence of Fiscal Decentralization on Economic Growth - Hendri, Hendri; Syofyan, Efrizal; Idris, Idris (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The purpose of this study is to know and analyze the influence of the local revenue, the balance fund, the capital expenditure and the private investment on economic growth. This research is an exploratory study conducted on 19 regency/city government in West Sumatera Province. Data analysis techniques are descriptive analysis, classical assumption test, and panel data regression analysis. The results of this study found that: 1) The local revenue of the region has no significant effect on economic growth, 2) the Balance fund has a significant positive impact on economic growth, 3) the Capital expenditure has a significant positive effect on economic growth, 4) the Private investment has a significant positive effect on economic growth.